(untitled) (Research, Society and Development, 2022)
Objective: To perform a narrative integrative review on non-conventional food plants (PANC), which present inhibitory action of the acetylcholinesterase enzyme, using for this the most consulted databases today; to list the metabolites identified in non-conventional food species with anticholinesterase application. Methods: Survey of articles that addressed studies of plants in the PubMed, Scielo, Tandfoline, Springer link, Scopus, ScienceDirect, and other academic search sites without language and year restriction, using the descriptors and DeCS (Descriptors in Health Sciences). Results: 128 studies were identified, of which 22 were selected for this review. Conclusion: The road to be traveled is long, so far, we do not know when a new drug will arrive to assist in the treatment of this disease, in the meantime several researches arise with purpose in the treatment, accessible of Alzheimer’s disease and this research will serve as a basis for future authors in the search for chemical markers for the treatment of Alzheimer’s and food plants.